Evolution of the Web: from Web 1.0 to 4.0 - Asaad Khaleel Ibrahim (Qubahan Academic Journal)
The internet has become a vital component of the twenty-first century as technology has advanced. The number of new technologies emerging in tandem with the qualities supplied by the Internet is rapidly increasing. The World Wide Web (WWW), which is commonly referred to as the world's largest information environment, is a vital virtual environment in which internet users may trade, read, and publish information using a Web browser. Web 1.0, Web 2.0, and Web 3.0 technologies have all been seen and are still being observed in this review paper. However, there is no clear definition for Web 4.0, which is a 4th generation web technology, in the literature. Web 4.0 has multiple dimensions, as seen by the first examples that have appeared. Big data, augmented reality, machine-to-machine communication (M2M), cloud computing, and artificial intelligence (AI) technologies, as well as smart agents, will be able to integrate in the future years. Web 4.0 is a web technology revolution that includes a new internet of things (IoT) that interacts with a variety of models. The goal of this study is to clarify the notion of Web 4.0, which is viewed as an intelligent and symbiotic (human-machine interaction) network with massive interfaces and linkages, as well as to contribute to the literature by studying its many dimensions and investigating its links with new generation technologies.